Modelos de valor presente como instrumentos para estimativa de preços de contratos de boi gordo, café arábica, milho e dólar norte-americano no Brasil - Silva, Carlos Eduardo Mariano da (2015)
The aim of this work is to test the rationality of the Brazilian market for commodities actively negotiated at the BM&FBovespa, the exchange for stocks and derivatives in Brazil. The study encompasses live cattle, arabic coffee, corn and the US$/R$ exchange rate. The Present Value Model (PVM) was used to test the ratio between the future and spot prices spread and the market price of commodity under study. The ratio between the convenience yield, that accrues to holders of inventory, and the spot price is also tested. Cointegration tests, Granger causality tests and serial autocorrelation are among the tools employed. Conformance to the present value model is weak, since there is no cointegration between the convenience yield and the spot price for none of the four commodities. Prices, therefore, deviate from fundamentals. It is not possible to reconcile return forecasts with an efficient market environment under a context of rational expectations for the above mentioned assets. It is thus necessary continued investigations in this field. Two alternative schools of thought for investigations would be using equilibrium models between future and spot prices with arbitrage finite elasticity and, if prices follow an stochastic multivariate process, reverting to a trend line, to treat the convenience yield as an endogenous variable.